(untitled) (Південний архів (історичні науки), 2025)
The study aims to examine the processes of preserving the memory of the fallen Kherson’s defenders in the context of the formation of the urban community’s local identity in the conditions of a full-scale war against Ukraine. The author pays special attention to oral history as a key method for collecting historical materials that allows for recording the vivid emotional memory of the relatives and families of those who died in the war. The study focuses on the mechanisms of collective memory formation, the transformation of local identities in the frontline city during the occupation in 2022, and the sociocultural significance of honoring the dead as a moral and uniting resource for the community. The methodological foundation includes oral history approaches, source analysis of interviews with local residents, critical analysis of memory narratives, and the elements of micro-history and historical anthropology. Special attention is paid to reconstructing the local war experience of Kherson residents through the prism of personal testimonies, which serve as an important source for interpreting not only the facts but also the value component of historical reality. The scientific novelty of the article lies in the focus on the specificity of local memory in the conditions of the ongoing war and the introduction of new empirical materials – Kherson residents’ oral testimonies about the events of the city defense in the first days of the invasion and the commemoration of the fallen – into scientific circulation. This allows us to take a fresh look at the role of memory as a factor in public mobilization, social unity, and national self-affirmation. The research revealed that preserving the memory of the fallen Kherson’s defenders is not just a historical task but an active factor in local identity formation based on shared experience, values, and moral responsibility. The article underscores the importance of integrating oral history into broader national historiographical and educational practices to preserve memory during wartime to the greatest extent. The conclusions underscore that preserving the memory of the fallen defenders not only performs the function of a moral duty to the past but lays the foundations for the future, through consolidating the values of resistance, dignity, and responsibility in the community’s collective consciousness. In this case, memory is not only the object of historical research but also an active social resource in the struggle for the nation’s identity and dignity.